Mechanism analysis of the solids holdup variations in downer reactors based on volumetric flux. (21st September 2019) - Lian, Wenhao; Pan, Xueer; Zheng, Shuang; Zhang, Wei; Zhang, Hui; Fushimi, Chihiro; Tsutsumi, Atsushi; Hao, Xiaogang; Huang, Wei; Guan, Guoqing
Highlights: Solids volumetric flux ( Vs ) is used to study the solids holdup in downers. Vs should be more appropriate to define the high-density operation. Limit operation conditions in the downer based on Vs are analyzed and defined. The RSM analysis method based on Vs is applied to analyze solids holdup variation. Abstract: Solids volumetric flux ( Vs ), which is expected to replace the solids mass flux ( Gs ) as the key factor influencing solids holdup in circulating fluidized beds, was proposed to investigate the solids holdup variation and predict the extreme operation conditions in the downers. In this work, by using more than 400 sets of experimental data from different literature in Response Surface Methodology (RSM) analysis, it is found that the overestimation of particle density effect on the solids holdup can be avoided by converting the Gs into Vs . Further studies indicated that the difference of solids holdup (Δ εs ) resulted from the different types of particles increased with the increase in Vs as well as the decrease in superficial gas velocity ( Ug ). Based on the normalized fitting results, the effects of different factors on the solids holdup were characterized. It is concluded that the effect extent was in the order of Vs  > Ug  >> particle size (dp ) > particle density (ρp ), which provided a guidance to control the solids holdup to satisfy the requirements in the downer by adjustment of various parameters, that is, Vs and Ug can adjust solids holdup roughly whereas dp and ρp can adjust solids holdup finely. Meanwhile, it is found that the upper limit of solids volumetric flux ( Vs, max ) can be increased by the increase of Ug, dp and/or ρp . In addition, it is considered that using Vs to replace Gs to define high-density operation in the downer could be more suitable in this study.